Hubungan BBLR dan Status Pemberian ASI Dengan Kejadian Stunting pada Baduta - Mariyami, Temtrem; Sanjaya, Riona (Utan Kayu Publishing, 2022)
According to the World Health Organization (WHO), around 162 million children under the age of 5 experience stunting and Indonesia becomes the fifth country in the country with stunting problems. The prevalence of stunting toddlers in Indonesia is still high, at 29.6%. According to Riskesdas the prevalence of Toddlers is Very Short and Short indicating that Central Lampung Regency is 52.68%. In Tanjung Rejo village in December 2018 there were 39 toddlers from 1,309 toddlers (2.98%) who experienced stunting conditions. The purpose of this study was to determine the relationship between LBW and the status of breastfeeding with the occurrence of Stunting in baduta in Tanjung Rejo Village, Pubian District, Lampung Tengah Regency in 2019. Type of analytic research and case control design. The population in this study were all mothers who had children under two years old (baduta) with ages 6-24 months in the area of Tanjung Rejo Village Pubian Subdistrict Central Lampung Regency totaling 91 mothers. The sample in this study amounted to 74 mothers. The analysis used was univariate with frequency distribution and bivariate using the chi square test. The results showed that LBW events was 9 baduta (12.16%), the status of ASI 2019 was 31 baduta (44.59%) which was not exclusive breastfeeding and the incidence of stunting was 15 baduta (20.27%). There is a correlation between the incidence of LBW and the incidence of Stunting with p value: 0.014 and OR: 6.875. There is a correlation between Exclusive breastfeeding status and stunting with p value: 0.027 and OR: 4,625. Based on these results it is suggested to campaign for the impact of LBW events, exclusive breastfeeding and prevention incidence of stunting promotion regarding Measles Rubella immunization in order to increase maternal knowledge and Measles Rubella immunization coverage. Abstrak: Menurut World Health Organization (WHO) sekitar 162 juta anak umur dibawah 5 tahun mengalami stunting dan Indonesia masuk menjadi negara urutan kelima dari negara dengan masalah stunting. Prevalensi balita stunting di Indonesia masih tinggi, yakni 29,6%. Menurut Riskesdas prevalensi Balita Sangat Pendek dan Pendek menunjukkan bahwa Kabupaten Lampung Tengah sebanyak 52,68%. Di Kampung Tanjung Rejo pada bulan Desember 2018 tercatat terdapat 39 balita dari 1.309 balita (2,98%) yang mengalami kondisi stunting. Tujuan penelitian ini untuk mengetahui hubungan BBLR dan Status Pemberian ASI dengan Kejadian Stunting pada baduta di Kampung Tanjung Rejo Kecamatan Pubian Kabupaten Lampung Tengah tahun 2019. Jenis penelitian analitik dan rancangan cross sectional. Populasi pada penelitian ini adalah seluruh ibu yang memiliki anak bawah dua tahun (baduta) dengan usia 6-24 bulan yang ada di wilayah Kampung Tanjung Rejo Kecamatan Pubian Kabupaten Lampung Tengah berjumlah 91 ibu. Sampel dalam penelitian ini berjumlah 74 ibu. Analisis yang digunakan adalah univariat dengan distribusi frekuensi dan bivariat menggunakan uji chi square. Hasil penelitian diketahui bahwa distribusi Frekuensi Kejadian BBLR sebanyak 9 baduta (12,16%), status pemberian ASI 2019 sebanyak 31 baduta (44,59%) yang tidak ASI Eksklusif dan kejadian stunting sebanyak 15 baduta (20,27%). Ada hubungan kejadian BBLR(p value: 0,014) dan status pemberian ASI Eksklusif (p value: 0,027) dengan kejadian stunting. Berdasarkan hasil tersebut disarankan kepada tenaga kesehatan khususnya puskesmas untuk mengkampanyekan dampak dari kejadian BBLR, pemberian ASI yang tidak eksklusif dan pencegahan kejadian stunting